The E domain of CRR2 participates in sequence‐specific recognition of RNA in plastids. Issue 1 (6th December 2018) - Ruwe, Hannes; Gutmann, Bernard; Schmitz‐Linneweber, Christian; Small, Ian; Kindgren, Peter
Summary: Pentatricopeptide repeat (PPR) proteins are modular RNA‐binding proteins involved in different aspects of RNA metabolism in organelles. PPR proteins of the PLS subclass often contain C‐terminal domains that are important for their function, but the role of one of these domains, the E domain, is far from resolved. Here, we elucidate the role of the E domain in CRR2 in plastids. We identified a surprisingly large number of small RNAs that represent in vivo footprints of the Arabidopsis PLS‐class PPR protein CRR2. An unexpectedly strong base conservation was found in the nucleotides aligned to the E domain. We used both in vitro and in vivo experiments to reveal the role of the E domain of CRR2. The E domain of CRR2 can be predictably altered to prefer different nucleotides in its RNA ligand, and position 5 of the E1‐motif is biologically important for the PPR–RNA interaction. The 'code' of the E domain PPR motifs is different from that of P‐ and S‐motifs. The findings presented here show that the E domain of CRR2 is involved in sequence‐specific interaction with its RNA ligand and have implications for our ability to predict RNA targets for PLS‐PPRs and their use as biotechnological tools to manipulate specific RNAs in vivo .